Pengembangan Usaha Produk Roti di UMKM A dengan Blue Ocean Strategy - Ashari, Asnita Yulfianti; Junus, Stella; Wolok, Eduart (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
MSME A is a manufacturing industry that operates in the food industry, especially the bread industry. The large number of developing bread MSMEs creates competition in the market. Therefore, it is necessary to develop a strategy to help MSMEs get out of the competitive zone (Red Ocean). The aim of this research is to identify the position of MSME A with the Blue Ocean Strategy and also to find out the bread development strategy within the scope of the Blue Ocean Strategy. Based on the results obtained, the market position of MSME A is below that of competing MSMEs or MSME A is in the competition zone (Red Ocean). This can be seen from the initial Canvas Strategy results where the recapitulation of marketing variables for MSME A is 2.92, while the recapitulation value of competing MSME marketing variables includes MSME B 3.80, MSME C 3.25, and MSME D 2.95. Therefore, seeing that the position of MSME A is still below that of competing MSMEs, it is necessary to develop a strategy to be able to create new markets so that they can get out of the competition zone (Red Ocean).